A dual response near-infrared fluorescent probe for hydrogen polysulfides and superoxide anion detection in cells and in vivo. (September 2015) - Yu, Fabiao; Gao, Min; Li, Meng; Chen, Lingxin
Abstract: Intracellular reactive sulfur species play important roles in physiological and pathological processes. Emerging evidences suggest that sulfane sulfur instead of H2 S is the actual signaling molecule in these processes. Sulfane sulfur can be generated as a result of the reaction between O 2 ·− and H2 S in mitochondria. Therefore, we develop a near-infrared mitochondria-targeting probe that allows multiresponse to O 2 ·− and H2 Sn successively for investigating this biosynthetic reaction. The probe exhibits highly selective fluorescent response to O 2 ·− and H2 Sn successively in presence of potential biological interferants. Fluorescent imaging studies and flow cytometry analysis of RAW264.7 cells elaborate that the probe can be used to reveal the continuous process of O 2 ·− burst and H2 Sn production in situ and in real-time. The mitochondria isolation indicates that the probe can specifically localize in mitochondria. Finally, the fluorescent probe has been successfully applied to detect O 2 ·− and H2 Sn in mice.